Host and bacterial factors linking periodontitis and rheumatoid arthritis - Krutyhołowa, Anna; Strzelec, Karolina; Dziedzic, Agata; Bereta, Grzegorz P.; Łazarz-Bartyzel, Katarzyna; Potempa, Jan; Gawron, Katarzyna (Frontiers in Immunology, 2022)
Observations from numerous clinical, epidemiological and serological studies link periodontitis with severity and progression of rheumatoid arthritis. The strong association is observed despite totally different aetiology of these two diseases, periodontitis being driven by dysbiotic microbial flora on the tooth surface below the gum line, while rheumatoid arthritis being the autoimmune disease powered by anti-citrullinated protein antibody (ACPA). Here we discuss genetic and environmental risk factors underlying development of both diseases with special emphasis on bacteria implicated in pathogenicity of periodontitis. Individual periodontal pathogens and their virulence factors are argued as potentially contributing to putative causative link between periodontal infection and initiation of a chain of events leading to breakdown of immunotolerance and development of ACPA. In this respect peptidylarginine deiminase, an enzyme unique among prokaryotes for Porphyromonas gingivalis, is elaborated as a potential mechanistic link between this major periodontal pathogen and initiation of rheumatoid arthritis development.